Numerical modeling of clamp load relaxation of plastic nuts under varying moisture and fiber contents - Wippermann, Jan; Meschut, Gerson (Welding in the World)
This study presents a numerical approach using a 3D finite element model to quantify the remaining clamp load of a plastic nut joint after a specific time. The viscoelastic relaxation of a thermoplastic nut, which is predominantly screwed on a welding stud, is described by a material card using Prony Series. Prony Series are derived from experimental dynamical mechanical analysis with different moisture and fiber contents of the thermoplastic. Since plastic nuts usually do not have preformed threads, the increased temperatures and resulting stresses from the thread-forming process are considered in the simulation. An FE model is created and verified by substrate stress relaxation tests. Experimental clamp load measurements with miniature compression load cells verify the clamp load prediction and show a good agreement. The developed model is used to analyze the clamp load distribution within the threads and reveals an almost even distribution within the threads.

Entwicklung einer Methode für die Prognose des Anziehdrehmoments von Kunststoffmutte - Wippermann, Jan; Meschut, Gerson (JOINING PLASTICS)

Ressourceneffiziente Füge- und Entfügetechnologien: Online-Content zum interaktiven Whitepaper KORESIL - Meschut, Gerson; Gilich, Julian; Chudalla, Nick Andre (Komplexität beherrschen, Kreisläufe schließen : Soziotechnische Systeme für ressourceneffiziente Leichtbaustrukturen ; Das interaktive Whitepaper)
Die Transformation der bisher linearen Wirtschaft zu einer Kreislaufwirtschaft und einer möglichst emissionsneutralen Herstellung und Verwendung von Produkten bedarf einer ganzheitlichen Forschung und Entwicklung in allen Bereichen der Prozesskette. Die Fügetechnik gilt dabei als Enabler moderner Hybridstrukturen und ermöglicht die anforderungsgerechte Verbindung artverschiedener Werkstoffe mit unterschiedlichen technisch-wirtschaftlichen Eigenschaftsprofilen. Aktuelle Herausforderungen umfassen das qualitätsgesicherte Fügen bei einer zunehmenden Materialvielfalt aus Primär- und Sekundärwerkstoffen sowie das gezielte Entfügen von Leichtbaustrukturen in Instandsetzungs- oder Recyclingprozessen. Ein weiterer Entwicklungsschwerpunkt liegt auf der menschzentrierten Ausrichtung von Arbeitsprozessen. So können Arbeitskräfte durch eine ergonomische Produktions- und Fügeprozessplanung sowie die Entwicklung und Einbindung prozessbegleitender Mixed-Reality-Technologien gezielt entlastet und dem derzeit zu verzeichnenden Fachkräftemangel effektiv begegnet werden. Das vorliegende Whitepaper zeigt aktuelle Herausforderungen in der Fügetechnik auf, fasst relevante Erkenntnisse und Lösungsansätze aus Industrie und Forschung sowie dem Verbundforschungsvorhaben „Konzepte für die ressourceneffiziente und sichere Produktion von Leichtbaustrukturen“ (KORESIL) zusammen und leitet geeignete Handlungsempfehlungen für die Industrie ab. Diese sollen beteiligten Anwendern strategische Ansätze aufzeigen, um Prozesse ressourceneffizienter und nachhaltiger gestalten zu können.

Effects of various process parameters in the joining process on the squeeze flow of highly viscous thermal interface materials - Gilich, Julian; Teutenberg, Dominik; Meschut, Gerson; Gröger, B.; Wiebicke, F.; Koch, I.; Gude, M. (Welding in the World)
Powertrain concepts incorporating renewable energies are an essential element of the energy revolution and increasingly require efficient manufacturing processes for electronic systems. Particularly, the joining of structures to be thermally coupled, such as the battery modules and the thermal management system (TMS), poses new challenges in process design. Factors that limit the process include the increased density, viscosity, and abrasiveness of thermal pastes as well as the pressure sensitivity of battery modules. The research presented aims to systematically investigate the influences of joining parameters on flow behavior, the formation of air inclusions, and the occurring joining forces to understand and systematically optimize the joining process. Employing a test setup following the Closing-Hele-Shaw-Cell, the influence of specific process parameters on the joining process such as the joining speed, joining gap, application pattern, and temperature was investigated for a silicone- and a polyurethane-based thermally conductive paste. The results indicate a high dependency of both the ensuing joining forces and the flow behavior on the parameters investigated. These insights imply a potential systematic parameter optimization and the specific adaptation of the joining process to improve flow behavior and reduce compressive stresses. This can ensure lower component deformations and qualify the process for the employment of cell types with a higher power density, a reduced encapsulation, and lower stiffness while at the same time improving production rates.

Komplexität beherrschen, Kreisläufe schließen: Soziotechnische Systeme für ressourceneffiziente Leichtbaustrukturen ; Das interaktive Whitepaper
Im Rahmen des BMBF-Forschungsvorhabens KORESIL wurden entlang einer beispielgebenden Prozesskette für hybride Leichtbaustrukturen notwendige Forschungs- und Entwicklungsschwerpunkte ermittelt. Insbesondere die Steigerung der Ressourceneffizienz und die Unterstützung des Menschen im Kontext zukünftiger Arbeitsumfelder standen dabei im Mittelpunkt der Arbeiten. Hierauf aufbauend konnten Handlungsempfehlungen für Wirtschaft, Wissenschaft und Politik abgeleitet werden. Das Projekt KORESIL ist eingebettet in das Projektnetzwerk des Forschungs- und Technologiezentrums für ressourceneffiziente Leichtbaustrukturen – FOREL. Dieses Zentrum wurde im Jahr 2013 als BMBF-Leuchtturmprojekt eingerichtet und ist eine offene, unabhängige Plattform zur Entwicklung von Hightech-Leichtbausystemlösungen in Multi-Material-Design für die Mobilität der Zukunft. Ziel der Plattform ist die Unterstützung von Entwicklungsprojekten, die Vernetzung der Leichtbauforschung innerhalb Deutschlands und die Zusammenführung verschiedener Förderinitiativen.

Investigation of local heat treatment strategies for a multi-range capable rivet and the influence on joint formation and load-bearing capacity - Holtkamp, Pia Katharina; Kappe, Fabian; Probst, Paula; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
To reduce CO 2 emissions, the industry, particularly in the mobility sector, focuses on lightweight vehicles with multi-material structures. As thermal joining processes are reaching their limits, mechanical techniques such as self-piercing riveting are being used. One innovative solution is the versatile self-piercing riveting process (V-SPR), which combines different material combinations with a multi-range rivet. 1 The joining process is divided into the piercing process and the forming process of the rivet head to the respective sheet thickness. The rivet shaft requires sufficient strength to punch through the punch-sided sheet, and sufficient ductility of the rivet head is required to form onto the punch-sided sheet. To achieve a combination of these requirements, local inductive heat treatment strategies are used for the rivet. To ensure reproducible rivet hardening, a specialised device has been developed for precise rivet positioning in the induction coil and the subsequent quenching process. The heat treatment differs in terms of hardening times and temperatures. In addition, the heat treatment is combined with a subsequent tempering process. The study aims to determine the resulting hardness distributions and microstructures of the rivet and to investigate the influence of different heat treatment strategies on joint formation and load-bearing capacities. The results show that a graded hardening profile has a positive effect on the spreading behaviour of the rivet foot and the forming behaviour of the rivet head. Furthermore, the load-bearing behaviour of the joints is increased.

Transient dynamic analysis: Performance evaluation of tactile measurement - Reschke, Gregor; Brosius, Alexander (Materials Research Proceedings)
Abstract. The assessment of mechanically joined connections, such as clinched connections, is usually conducted destructively. Applicable non-destructive testing methods like computed tomography are time-consuming and costly, or, like electrical resistance measurement, provide only a limited amount of information. A fast, non-destructive evaluation of the joints condition shall be made possible by using transient dynamic analysis (TDA). It is based on the introduction of sound waves and the evaluation of the response behavior after passing through the structure. This study focuses the application of TDA to clinched shear connections to evaluate the performance of the tactile measuring setup. Twenty-one series were investigated, covering variations in joining task, manufacturing and defect. The evaluation was carried out using machine learning to determine for which series characteristic signals may be detected. It was shown that a classification of the investigated specimens is possible, whereby the classification accuracy depends on the examined variation. Furthermore, the accuracy was evaluated as a function of frequency and results were concluded to identify the limits of the used measuring setup.
Keywords: Joining; Machine Learning; Transient Dynamic Analysis

Data driven prognosis of clinch joints in multi-material design - Ludwig, Jean-Patrick; Tsi-Nda Lontsi, Seraphin; Neumann, Jonas; Kappis, Lukas; Scharr, Christian; Flügge, Wilko; Merklein, Marion; Meschut, Gerson (Materials Research Proceedings)
Abstract. Clinching is a conventional mechanical joining process used in Multi-Material Design in the automotive sector. To receive the desired geometrical characteristics in clinch joints, correct process design is required. To reduce the cost of finding fitting process parameters, numerical simulation of the joining process can be used to predict the geometrical characteristics, such as interlock, instead of an experimental approach. These numerical simulation models consume computational resources and time. In this paper machine learning is used to find correlations between features of the joining process and geometrical characteristics in the joint. This serves the purpose of predicting the joint’s target values more resource-efficiently. Modelling with machine learning requires a structured dataset with sufficient parameter variation. To create this data base the following procedure was used. For joining partners, a HC340LA steel alloy with 2 mm material thickness was used punch-sided and an EN AW 5182 aluminum alloy with 1.5 mm thickness was used die-sided. For this combination a suitable tool combination and punch distance was experimentally identified. A finite element model was created to reproduce the joining process. For the modelling of the material of both joining partners flow curves determined by Vallaster et al. were used [1]. The punch and die were recreated digitally by opto-electronic measurements and transformed into a mesh suitable for numerical simulation. The model was validated by comparing process values like the maximum force applied by the punch and geometrical values in the joints cross section. Additionally, a process window for suitable punch distances was experimentally determined. Afterwards a variation of 70 different process designs was conducted with variants inside and outside the process window. The results were used for training, testing and validating various machine learning models. All models competed against each other to find the must suited model to predict every geometric value. To ensure good model performances and prevent the model from overfitting, a tenfold cross validation was used for validating the models. Analysis of the results gives the following key findings: i) Good predictability is reached for the interlock and sheet thickness of the joint. ii) Prediction neck thickness showed low error values, but also low correlation. iii)The prediction of those key values for evaluating clinch joint characteristics by machine learning models positively impacts needed resources in comparison to numerical models.

In situ computed tomography – Analysis of settling effects during single-lap shear tests with clinch points - Köhler, D.; Troschitz, J; Kupfer, R.; Gude, M. (Materials Research Proceedings)
Abstract. In the field of mechanical engineering, destructive tests such as shear tests of mechanical joints are usually followed by imaging methods such as microsectioning or computed tomography (CT). They can help to interpret the measured load-displacement curves, analyze the failure behavior and validate numerical models. However, due to unloading, springback effects and crack closures can occur, which influence the state of the investigated specimen. In this context, in situ CT is able to explore the testing process with a specimen under load avoiding these influences. For in situ CT investigations, the displacement increase is interrupted at certain stop points. While the displacement is kept constant, the CT scan is performed. However, it was observed that the reaction force reduces during CT scanning, e. g. due to settling effects in the test setup. Although in situ CT is established now in research, little attention is paid to the uncertainties which arise from the discontinuous testing procedure. This study systematically explores the impact of these interruptions on the load-displacement behavior and the geometry of clinch points during tensile shear testing. To quantify the influence of the interruptions, loads at defined displacement levels and the final geometry are evaluated statistically. We found, that the load-displacement behavior of both test groups is similar. Despite some small but significant statistical deviations of the loads and the final geometry, our results show that, discontinuous testing has a high level of significance for the phenomena overserved in shear tests with clinch points.

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gilich, Julian; Meschut, Gerson; Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Verfahrenserweiterung des Widerstandselementschweißens für stahlintensive Dreiblech-Hybrid Mischverbindungen mit zwei höchstfesten Stahlgüten in Mittel- und Basislage - Heitmann, Marcel; Meschut, Gerson

Experimentelle und numerische Untersuchung des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Meschut, Gerson; Gilich, Julian; Gude, Maik; Koch, Ilja; Gröger, Benjamin; Wiebicke, Felix

Application of distributed fiber optic sensing for defect detection in adhesive bonds - Hermelingmeier, Lucas; Teutenberg, Dominik; Meschut, Gerson

Entwicklung eines methodischen Ansatzes zur Vermeidung der Spritzerbildung beim Widerstandspunktschweißen durch multiparametrische Prozessanalyse mittels künstlicher Intelligenz - Meschut, Gerson; Yang, Keke; Rethmeier, Michael; El-Sari, Bassel

Bruchmechanisches Schnittebenenkonzept zur lebensdauergerechten Auslegung von hyperelastischen Klebverbindungen bei multiaxialen und variablen Belastungsamplituden - Buczek, Moritz; Duffe, Tobias; Kullmer, Gunter; Tews, Karina; Teutenberg, Dominik; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Berücksichtigung des Einflusses fertigungsinduzierter Vorverformungen warmaushärtender Klebstoffe auf die Schwingfestigkeit geklebter Verbindungen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Methodenentwicklung zur Simulation von hyperelastischen Klebverbindungen unter Crashbelastung - Schmelzle, Lars; Beule, Felix; Possart, Gunnar; Teutenberg, Dominik; Mergheim, Julia; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Methodenentwicklung zur Ermittlung lokaler Klebschichtzustände innerhalb struktureller Verbindungen - Hermelingmeier, Lucas; Teutenberg, Dominik; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimentelle und numerische Untersuchungen zur Alterung von Klebverbindungen unter zyklischer und hygrothermischer Beanspruchung im Stahl- und Anlagenbau - Neubert, Fynn Lucas; Teutenberg, Dominik; Meschut, Gerson; Rodschei, Maxim; Mergheim, Julia (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Mechanical joinability of microstructurally graded structural components manufactured from hypoeutectic aluminium casting alloys - Neuser, Moritz; Schlichter, Malte Christian; Hoyer, Kay-Peter; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (44th Conference of the International Deep Drawing Research Group (IDDRG 2025))
Lightweight design is a driving concept in modern automotive engineering to minimize resource consumption over a vehicle's lifecycle through multi-material design, which relies on the use of joining techniques in car body fabrication. Multi-material design and the increasing trend towards producing large structural components using the megacasting process pose considerable challenges, particularly in the mechanical joining of aluminium-silicon (AlSi) castings. These castings typically exhibit low ductility and are prone to cracking when mechanically joined. Based on the excellent castability of hypoeutectic AlSi alloys, these are applied in sand casting and die casting as well as in megacasting. With a silicon content between 7 wt% and 12 wt%, these AlSi-alloys have a plate-like silicon phase that initiates cracks during mechanical joining. To enhance the joinability of castings, the research hypothesis is that improved solidification conditions enable a significant modification in the microstructure and therefore, increase the mechanical properties. During the manufacture of the castings using the sand casting process, the solidification conditions within the structural elements are varied to modify the microstructure to obtain castings with graded microstructure. The castings are evaluated using mechanical, microstructural and joining testing methods and finally, a microstructure-joinability correlation is established.
Keywords: Joining; Casting; Self-pierce riveting; Aluminium casting alloy